Diagnostic des Défauts de Cage Rotorique d’un MAS en Utilisant RMxpert & ANSYS-Maxwell - GHOZLANE Ismail; DJABRI Achoura; BENLARBI Keltoum (UNIVERSITE Amar Telidji de Laghouat.FACULTE DE TECHNOLOGIE.DEPARTEMENT D’ELECTROTECHNIQUE, 2022)
The aim of this memoir is the diagnosis of bar break faults in three-phase squirrel-cage induction motor (IM) by a simulation model based on a 2D finite element method. We started by establishing a state of the art on the diagnosis of IM faults. Then, we used ANSYS-RMxprt software to characterize the studied motor with a power of 30 kW. And finally, the ANSYS-Maxwell 2D software, has been used to simulate the machine in normal and in faulty modes. The FFT spectral analysis technique of stator current and speed has been successfully used to diagnose bar break faults in the studied asynchronous machine